Review of taxation policies in the EU member states (Publications Office of the European Union, 2021)
This report describes and assesses progress by EU Member States in bringing their tax policies in line with the EU's main tax priorities to: foster innovation and productivity, thus supporting an EU economy that is fit for the digital and global challenges; pave the way for environmental sustainability and good public health, thus contributing to climate-neutral and more resilient economies; fight tax fraud, evasion and abuse, thus ensuring that everybody pays their fair share; and contribute to social fairness and prosperity, thus ensuring an economy that works for people and addresses their needs. With those priorities in mind, this report identifies relevant indicators and potential improvements of tax systems in terms of tax design, implementation and compliance. The report finds that taxation can play a key role in supporting Europe's recovery. The COVID-19 pandemic has created a severe crisis in Europe and the world. Citizens face an increased risk of poverty, our public health systems have been put under stress, many companies are over-leveraged, and tax revenue is likely to decrease in the coming years due to the pandemic. Member States should take the recovery as an opportunity to reform their fiscal framework and to address challenges brought by climate change, environmental degradation, ageing of population, digitalisation and globalisation. A well-designed tax policy response can help to increase fairness and generate much needed and sustainable revenue to recover from this crisis. It can also help foster innovation and productivity to improve the resilience of our economies and restore a more solid capital structure.
10.2778/979530
Keywords: Graue Literatur; Steuerpolitik; Steuersystem; Steuerreform; EU-Staaten; tax system; tax; fiscal policy; economic survey; tax reform; EU Member State